The Chemical composition of leaf oil of Cupressus tonkinensis Silba. in Huu Lien, Lang Son province - Thai, Tran Huy; Hien, Nguyen Thi; Minh, Do Thi; The, Pham Van (Academia Journal of Biology, 2012)
Cupressus tonkinensis Silba. is an evergreen, medium-sized tree, up to 15-25 cm in height. Bark is gey brown with longitudinal fissures. Leaves are scaly, closely inserted on twigs. Cones are unisexual, grouped on a stalk. Male cone is subglobular. This is an endangered species in Vietnam, only found in a narrow area of the Central Region and the North belonging to Lang Son and Tuyen Quang provinces. This is a light-demanding species, thriving in hot and wet tropical and subtropical forests and occurring naturally as dominant stands at elevation of 800-1200 m. The yield of essential oil from the air-dried leaves was 0.13 percent. By using GC/MS analysis, 26 constituents have been identified. The main constituents of essential oil were sabinen (29.34%), a-pinen (25.4%), 4-terpineol (13.91%) and g-terpinen (5.5%).